LANGUAGE CHANGING IN NOVEL BIRU BY FIRA BASUKI - Anggraini Thesisia Saragih (UIN Sumatera Utara, 2017)
This study deals with feminism perspective based on novel. The author is also woman, namely Fira Basuki. The novel tells us about the relationship of women and men with conflicts and love. The problem is how about the language changing in that novel that influences feminism perspective. The objective of this study is to find out about the language changing in that novel with variation language. The study used qualitative method. The data was the dialogues some characters in that novel that use Indonesian language. The researcher found three changes and variation of languages in that novel. They are Indonesian language that change into slang, Indonesian language that change into foreign language, and Indonesian language that change into local language. So the conclusion of this study is in this modern era, the woman tends to use the variation of language to maintain their existences in the society.